Penerapan Teknologi Surimi dari Tetelan Ikan Tuna dan Pengolahan Produk Kaki Naga - Dwight Soukotta; Theodora EAA Matrutty; Beni Setha; Alfonsina Marthina Tapotubun; Jusuf Leiwakabessy; Johanna Tupan (Institute for Research and Community Services, 2023)
The tuna loin industry leaves quite a lot of waste in the form of thin meat tether mixed with fiber. Tuna tethers have good development prospects because they can become the main ingredient for making surimi. Surimi is an intermediate product that has a high functional protein content and has been recognized worldwide. Surimi is the raw material for fish jelly products such as dragon leg, meatballs, nuggets, and others. Based on observations, it turns out that tuna tethers have not been optimally utilized to improve the welfare of the community. The North Ambon Island Klasis area community does not know the processing of surimi and its development opportunities into various competitive products. The purpose of this activity is to utilize tuna tether through the application of surimi technology and dragon foot product processing to household wives from several villages on North Ambon Island. The target audience for this activity was 30 household wives from 17 villages in the North Ambon Island Klasis area. The activities were carried out from March to April 2022, consisting of three (3) stages , preparation, implementation of counseling, and training. The results of the paired sample T test show that there is a significant difference in the knowledge of the target audience before and after the implementation of counseling and training on the application of surimi technology and processing surimi into dragon foot products. The average post-test score of 30 participants increased by 59.39% after participating in counseling and training activities on the application of surimi technology and processing surimi into dragon foot products. At the end of the activity, the participants practiced surimi and dragon foot processing trials, showing 90% of the participants were quite skilled in processing the two products.